SAT0480 Comparative effectiveness of secukinumab and infliximab in psoriatic arthritis assessed by matching-adjusted indirect comparison using pivotal phase 3 clinical trial data. (15th June 2017) - Strand, V; McInnes, I; Mease, P; Choy, E; Nash, P; Thom, H; Kalyvas, C; Gandhi, K; Pricop, L; Jugl, S
Abstract : Background: Therapeutic options with discrete modes of action are now available for psoriatic arthritis (PsA). Clinicians require evidence to guide decision-making. No head-to-head RCTs have compared secukinumab 150 mg (SEC; anti-IL-17A) with infliximab 5 mg/kg (INF; TNFi) in patients with PsA. Matching-Adjusted Indirect Comparison (MAIC) can be used to estimate comparative effectiveness and enables treatment outcomes to be compared across effectively balanced trial populations. MAIC is an established method in health technology assessments, with NICE having recently published guidance. Objectives: To use MAIC to assess the comparative effectiveness of SEC and INF for up to 1 year using pooled FUTURE 1 (F1) and FUTURE 2 (F2) individual patient data (IPD) and published aggregate IMPACT 2 data, respectively. Methods: Pooled F1 and F2 data were used to maximize the effective sample size (ESS) for SEC. IPD from the SEC arms of F1 and F2 (n=302) were weighted to match selected baseline characteristics of the INF arm of IMPACT 2 (n=100). Placebo arms were also matched; placebo-adjusted comparisons were possible only until week 16 because patients could receive active treatment from this time point onwards. Logistic regression was used to determine weights for age, sex, race, body weight, methotrexate use, presence of psoriasis (≥3% body surface area), mean PASI score, dactylitis, enthesitis, mean HAQ-DI score and previous TNFi therapy. Recalculated outcomes from F1 and F2 (SEC, ESS=91; placebo, ESS=59) were compared with data from IMPACT 2 (INF, n=100; placebo, n=100). Pairwise comparisons using odds ratios (ORs [95% CIs]) were performed for ACR 20, 50 and 70 responses at nearest-equivalent time points across trials: weeks 6/8, 14/16, 24 and 54/52. Mean changes from baseline in SF-36 Physical and Mental Component Summary (MCS) scores were also compared. Strict thresholds were avoided when interpreting p values, in line with American Statistical Association 2016 guidance. Results: There was no evidence of differences in ACR 20, 50 and 70 responses between SEC and INF at weeks 6/8, 14/16 (both placebo-adjusted) and 24 (non-placebo-adjusted). At week 54/52, ACR 20 and 50 responses were higher with SEC than INF (OR [95% CI]: 4.05 [1.98–8.30], p <0.001 and 1.90 [1.05–3.44], p =0.034, respectively). Improvements in SF-36 MCS scores were greater with SEC than INF at weeks 14/16 ( p =0.063), 24 ( p =0.001) and 54/52 ( p <0.001). A sensitivity analysis that added PsA duration, swollen joint count and CRP levels to the matching parameters yielded similar results. Conclusions: In this MAIC, SEC showed evidence of superiority for symptomatic improvement (non-placebo-adjusted ACR 20 and 50) over INF for active PsA at 1 year. This was accompanied by greater improvements in SF-36 MCS scores. At earlier time points, there was no evidence of differences in ACR responses between SEC and INF. Disclosure of Interest: V. Strand Consultant for: Abbvie, Amgen, AstraZeneca, Biogen Idec, Boehringer Ingelheim, Celltrion, Crescendo, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi and UCB, I. McInnes Consultant for: Abbvie, Celgene, Janssen, Novartis, Pfizer and UCB, P. Mease Grant/research support from: AbbVie, Amgen, BMS, Lilly, Novartis, Pfizer and UCB, Consultant for: AbbVie, Amgen, BMS, Corrona, Lilly, Merck, Novartis, Pfizer, Sun and UCB, Speakers bureau: AbbVie, Amgen, Celgene, Genentech, Novartis, Pfizer and UCB, E. Choy Grant/research support from: Pfizer, Roche and UCB, Consultant for: Chugai Pharma, Eli Lilly, Janssen, Novartis, Pfizer, Regeneron, Roche, R-Pharm and Sanofi, P. Nash Grant/research support from: Novartis, Consultant for: Novartis, Speakers bureau: Novartis, H. Thom Consultant for: Eli Lilly, F Hoffman-La Roche, Novartis Pharma AG and Pfizer, C. Kalyvas Employee of: Paid employee of the Mapi Group. The Mapi Group received funding from Novartis Pharma AG for this study, K. Gandhi Employee of: Novartis employee with stock, L. Pricop Employee of: Novartis employee with stock, S. Jugl Employee of: Novartis employee with stock